Islamic Economic Development Model Based on Waqf Institutions in Minority Communities - Sukree Langputeh; Umar Akem; Mutathahirin Mutathahirin; Ahmad Suryadi; Nuha Sufina Binti Saidi (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The economic development of Muslim minority communities faces ongoing challenges, including limited access to business capital, weak Islamic economic institutions, and the underutilisation of waqf assets as a tool for empowerment. A promising alternative is the establishment of waqf-based institutions that integrate the principles of ta’awun (mutual assistance), justice, and sustainability within the Islamic economy. This study aims to formulate a model of Islamic economic development through waqf institutions as instruments of empowerment for Muslim communities. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, documentation, and analysis of institutional documents. Data analysis employed an interactive model comprising data reduction, data presentation, and drawing of conclusions. The research findings indicate that the economic development model of waqf institutions is structured around five key components: i) the management of productive waqf funds, ii) the implementation of a Sharia-compliant cooperative system, iii) the empowerment of members’ micro-enterprises, iv) the strengthening of Islamic economic education, and v) transparent institutional governance. This model improves access to Sharia-based financing, expands entrepreneurial opportunities, strengthens social solidarity, and promotes sustainable economic growth. This study contributes to the scientific literature on the optimisation of productive waqf through an institutional framework as a replicable model of Islamic economic development for Muslim minority communities worldwide.